PERILAKU SEKSUAL PADA REMAJA DI SMA NEGERI 01 KETANGGUNGAN KECAMATAN KETANGGUNGAN KABUPATEN BREBES - Intan Monik Pratami; Dea Riskha Fitriliana; Haifa Faikhatus Zakiyah (Midwifery Care Journal, 2022)
On duty health Brebes declare for that IMS'S case amount in july global ala September at Intermediate Javanese Province available 2761 IMS'S patient case, meanwhile at Brebes's Regency exists 19 IMS'S patient case. This research intent to know some factor which regard sexual behaviour on adolescent one covers oldster social support, coeval friend and mass media. This observational type is analytic by use of design cross sectional . Population is exhaustive student braze x SMA Country to Brebes's Regency responsibility total one 148 respondents. Sample tech that is utilized is purpossive is sampling . Intrumen is kuesioner's data collecting. Suggested to student and suggest school party in particular for sekaolah's student and party wants to get introspection in give monitoring and guidance and good instruction for schoolgirl student developing its to reach degree health which optimal.